Electrical Characterization of an Atmospheric Pressure Plasma Jet - KC, S. K.; Sharma, S.; Shrestha, R.; Subedi, D. P. (Journal of Nepal Physical Society, 2019)
In this work, a plasma jet has been generated with capillary tube having external diameter 4.0 mm and thickness 1.0 mm. Argon has been used as a working gas. The electrical characteristics of this device like instantaneous power, and discharge current have been measured. The effects of applied voltage on the dissipated power of the device have been investigated. The current is measured with the current probe whereas the voltage is measured from the locally fabricated voltage divider having ratio 1201:1. The electron density has been found out using power balance method. In addition, the power consumption during the discharge has also been studied with the help of Lissajous Figures. The calculated power consumption has been compared with other manual as well as I-V plots.